Ricardo Palma's contributions to national identity - Huárag Álvarez, Eduardo (2023)
This paper examines four Ricardo Palma’s traditions in the light of his contributions to Peruvian national identity. In these traditions, the narrator records the way of being, thinking and acting of the criollo class of the republic, successors of the viceroyalty and the heroes of the conquest. This portrait of criollo habits and ideology constitutes one of Palma’s important contributions to the identity of the Peruvian nation. Keywords: national identity, orality, criolla ideology, The Royal Commentaries, popular sayings.